Aggressive Metastatic Inflammatory Myofibroblastic Tumor After Allogeneic Stem Cell Transplant With Fatal Pulmonary Toxicity From Crizotinib. Issue 8 (November 2016) - Shash, Hwazen; Stefanovici, Camelia; Phillips, Susan; Cuvelier, Geoffrey D.E.
Abstract : Inflammatory myofibroblastic tumors (IMTs) are rare tumors with an intermediate spectrum of biological behavior. IMTs are uncommon secondary malignancies after hematopoietic stem cell transplant. The presence of anaplastic lymphoma kinase rearrangements in 50% of IMTs has led to therapeutic trials with crizotinib, although limited experience remains with crizotinib use in children. We describe the first reported case of a highly aggressive and metastatic IMT (secondary malignancy) in an 8-year-old girl following umbilical cord blood transplant. Although tumor response was demonstrated with anaplastic lymphoma kinase inhibition, she later developed fatal pulmonary toxicity from diffuse alveolar damage, a feature felt most likely to be due to crizotinib.